All that glitters - Steel, Danielle (New York : Delacorte Press, 2020)
"When her life of privilege is upended by a terrorist attack that ends her parents' lives, a college senior struggles to rebuild on her own terms, learning uplifting and heartbreaking life lessons throughout a series of relationships and opportunities." --
Keywords: Families -- Fiction; Grief -- Fiction; Friendship -- Fiction; Success -- Fiction; Orphans -- Fiction; Crime victims' families -- Fiction; Interpersonal relations -- Fiction; Rich people -- Fiction; Bildungsromans